2005
DOI: 10.1038/sj.sc.3101795
|View full text |Cite
|
Sign up to set email alerts
|

Bowel management in patients with spinal cord injury – a multicentre study of the German speaking society of paraplegia (DMGP)

Abstract: Study design: A descriptive, cross-sectional, multicentre design was used. Objective: To analyse bowel management in patients with spinal cord injury (SCI) especially the occurrence of unplanned bowel evacuations and duration of planned bowel evacuation. Setting: In total, 29 rehabilitation facilities for SCI patients in Austria, Germany, the Netherlands and Switzerland, with a total of 837 hospitalized SCI patients. Method: Data were collected by nurses within 1 week in November 2001 using a quantitative ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 20 publications
2
28
1
Order By: Relevance
“…Furthermore, it has been reported that manual removal of stool is associated with low risk of unplanned bowel evacuation and short duration of evacuation time. 24 In this study, 29.8% of the patients used manual removal of stool. The use of this method by patients with SCI at or above the T6 level should require topical anesthesia to prevent AD reactions.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, it has been reported that manual removal of stool is associated with low risk of unplanned bowel evacuation and short duration of evacuation time. 24 In this study, 29.8% of the patients used manual removal of stool. The use of this method by patients with SCI at or above the T6 level should require topical anesthesia to prevent AD reactions.…”
Section: Discussionmentioning
confidence: 91%
“…16 Limited understanding of the need for this intervention has resulted in difficulties for SCI individuals when nursed in general hospitals, 17 and the community. However, manual evacuation is associated with shorter duration of bowel care 3,8 and it is the most common intervention among UK communitybased SCI individuals. 3 It is acceptable to SCI individuals because it is an effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Development of an individual program depends on the experience of the health-care practitioner and trial and error. Use of manual evacuation of stool is reported in 8-68% [1][2][3]8,9 but there is little evidence of the need for and acceptability of the procedure. 10 Anecdotally it is regarded as invasive and may be unacceptable to patients, carers and staff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 There are also patients with SCI who are able to initiate defecation when they sense an urge. The size of this group was found to be 12% of 837 patients in one study 11 and 20% of 171 patients in another. 10 There are also patients with SCI who perceive sensations of bowel activities associated with symptoms of an autonomic dysreflexia, visceral pain, non-painful sensations and phantom phenomena.…”
Section: Introductionmentioning
confidence: 81%